Liquid Biopsies - the Clinics and the Molecules - Kubaczková, V; Sedlarikova, L; Bollová, B; Sandecká, V; Stork, M; Pour, L; Sevcikova, S (Klinicka onkologie, 2017)
Unlike bone marrow biopsies, liquid biopsies represent a gentler, more accessible, less painful, repeatable and more comprehensive approach to get biologically relevant information about the entire tumor but also about treatment response and level of minimal residual disease. This is all possible since peripheral blood contains not only circulating tumor cells but also many circulating molecules of nucleic acids (microRNA, cell-free DNA, long non-coding RNA etc.). Multiple myeloma is a genetically heterogeneous disease characterized by multifocal tumor deposits in the bone marrow but also focal lesions elsewhere. Single-site biopsy of the bone marrow creates a sampling bias that provides a limited molecular profile as the biopsy cannot capture all subclones. Moreover, during disease progression and treatment, molecular profile is changed and subclones of multiple myeloma cells resistant to treatment are formed. Likewise, various clones found in extramedullary sites that are not present in the bone marrow respond differently to treatment directly influencing survival of patients. Thus, liquid biopsies seem to be a relevant and necessary next step for diseases such as multiple myeloma.Key words: multiple myeloma - minimal residual disease - prognosis - liquid biopsies - cell-free DNA - non-coding RNA.
Keywords: Liquid Biopsy; Multiple Myeloma; RNA, Untranslated; mnohočetný myelom; reziduální nádor; Neoplasm, Residual; Bone Marrow; Humans; lidé; tekutá biopsie; Cell-Free Nucleic Acids; nekódující RNA; volné cirkulující nukleové kyseliny; kostní dřeň